Monitoring of Foreign Drug Safety Information - Editorial article (Безопасность и риск фармакотерапии, 2019)
Analysis of administrative decisions of foreign regulatory authorities on the recoil of medicines and/or the need for changes in the instructions for their medical use due to changes in the safety profile, conducted by experts of the Scientific Centre for Expert Evaluation of Medicinal Products revealed 23 administrative decisions. These decisions contained information on the following medicines registered in Russia: аmitriptyline, duloxetine, quetiapine, lamotrigine, topiramate, phenytoin, articaine, epinephrine, bupivacaine, oxybutynin, dexlansoprazole, pantoprazole, esomeprazole, famotidine, ketoconazole, minocycline, quinolone and fluoroquinolone (cinoxacin, ciprofloxacin, flumequine, levofloxacin, lomefloxacin, moxifloxacin, nalidixic acid, norfloxacin, ofloxacin, pefloxacin, pipemidic acid, prulifloxacin and rufloxacin), antiretrovirals (abacavir, abacavir, dolutegravir, lamivudine, zidovudine, atazanavir, cobicistat, emtricitabine, tenofovir, darunavir, didanosine, rilpivirine, efavirenz, enfuvirtide, etravirine, fosamprenavir, indinavir, lopinavir, ritonavir, maraviroc, raltegravir, rilpivirine, nevirapine, saquinavir, tipranavir), direct-acting antiviral drugs (daclatasvir, dasabuvir, elbasvir, grazoprevir, glecaprevir, pibrentasvir, sofosbuvir, ombitasvir, ritonavir).